Coronavirus in News Text: Critical Discourse Analysis Detik.Com News Portal - Ida Ismiyati; Rida Nurlatifasari; Sumarlam Sumarlam (Yayasan Visi Intan Permata, 2021)
At this time the whole world is being attacked by a virus called the Corona Virus or Severe Acute Respiratory Syndrome Corona Virus 2 (SARS-CoV-2) is a type of virus that attacks the human respiratory system. This disease due to viral infection is called COVID-19. COVID-19 is a polemic that causes concern for the community due to its rapid spread and even causes many deaths, including in Indonesia. The condition of this social situation makes a lot of news done, one of which is related to prevention with social distancing published by Detikcom. This study aims to conduct a critical analysis of articles about COVID-19 on Detikcom. This research uses a descriptive method. The object of the research is an article entitled